ATIM-27. TUMOR MUTATIONAL BURDEN PREDICTS RESPONSE TO ONCOLYTIC POLIO/RHINOVIRUS RECOMBINANT (PVSRIPO) IN MALIGNANT GLIOMA PATIENTS: ASSESSMENT OF TRANSCRIPTIONAL AND IMMUNOLOGICAL CORRELATES. (11th November 2019) - Gromeier, Matthias; Brown, Michael; Beuabier, Nike; Yan, Hai; He, Yiping; Zhang, Gao; Desjardins, Annick; Herndon, James; Bolognesi, Dani; Friedman, Allan; Friedman, Henry; McSherry, Frances; et al.
Abstract: BACKGROUND: The live attenuated oral poliovirus vaccine was modified to contain a heterologous internal ribosomal entry site stemming from human rhinovirus type 2, creating PVSRIPO. PVSRIPO recognizes CD155, an oncofetal cell adhesion molecule and tumor antigen widely expressed ectopically in malignancy. We have previously reported that deep sequencing of biopsy material obtained prior to PVSRIPO infusion confirmed that a very low mutational load is associated with longer survival. METHODS: Patient tumor material from both phase I and 2 clinical trials was collected pre PVSRIPO. When available, post-treatment tissue from longitudinal samples were also collected. Tissue was subjected to RNA sequencing, histological analysis, and flow cytometry analysis. RNAseq analyses were performed comparing pre- and post- treatment expression profiles and computational predictions of tumor immune composition deciphered changes after PVSRIPO therapy. Histology and flow cytometry quantitated myeloid, CD8/4/regulatory T cell densities, and other immune cell types after treatment and compared to baseline tissue similarly analyzed to detect changes. RESULTS: To date, analysis of phase 1 trial data has demonstrated a correlation between low TMB and increased markers of immunological gene expression profiles. This trend was not observed in TCGA samples that were almost exclusively primary GBM suggesting and interplay with prior therapy or evolution with recurrence. CONCLUSION: Our findings presented here suggest that response to PVSRIPO therapy, and possibly that of other modalities engaging innate antiviral signatures in situ, may be dependent upon prevailing tumor microenvironment composition/status at the time of treatment.